2009
DOI: 10.1097/ccm.0b013e31819ced3a
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and hematoma volume in acute intracerebral hemorrhage

Abstract: Anemia is common in acute ICH and its presence at admission is an independent predictor of larger volume of ICH. Given the central role of ICH volume in outcome, clarification of the mechanisms underlying this relationship may offer novel therapeutic targets for reducing ICH morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
85
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 31 publications
9
85
1
1
Order By: Relevance
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…There were also 2 studies that did not state the design 21, 26. There was a high degree of diversity in geographic location, with cohorts from Germany,8, 19, 25 Switzerland,16, 20 the United States,18, 24 the People's Republic of China,2, 22 Canada,23, 28 India,6 Israel,10 the Republic of Korea,9 Denmark,21 Taiwan,17 the United Kingdom,26 and Poland 7. In addition, 2 studies were conducted across multiple countries 1, 27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations